Effect of Seed Priming on Yield and Biochemical Characteristic of Wheat in Sodic Soil of Eastern Uttar Pradesh - Yadav, R. K.; Pandey, Amit Kumar; Kewat, R. N.; Gopal, Ram (International Journal of Bio-resource and Stress Management, 2016)
Field experiments were conducted at Main Experimental Station, N.D. University of Agriculture and Technology, Kumarganj, Faizabad to evaluate the effect of pre-sowing treatments on yield and biochemical characteristic of Wheat in Sodic Soil. Seed priming is a low risk technology to improve poor crop establishment. It improves seed germination, emergence and seedling growth by altering seed vigor, dormancy and the physiological state of the seed. It improves germination by repairing damaged proteins, RNA and DNA of low vigor and aged seeds that may accumulate during seed development. Germination percentage (%) was observed higher in the seeds primed chemical and plant growth regulators (PGRs). Maximum germination percentage (%) was observed in the treatment halo priming with 3% KNO3 (93%) while minimum in non primed control treatment (78%). Seed priming enhanced the yield and yield components (no. of spikes m-2, no. of grains plant-1, 1000 seed weight and grain yield q ha-1). The maximum increase in all the yield contributing traits were observed with KNO3 (3%) followed by Salicylic acid (100 ppm), KNO3 (1%) and salicylic acid (50 ppm) as compared to control. Seed priming treatments significantly affected dry biomass plant-1. Maximum dry biomass plant-1 was recorded with KNO3 (3%) followed by salicylic acid (100 ppm), and 1% KNO3. It was concluded that seed priming with 3% aqueous solution of KNO3 is the effective seed priming technique to improve growth and yield of wheat under sodic soil condition.